Development of Arabic Language Learning Syllabus - Nafi’i, Wildan (Global Education Journal, 2025)
A well-designed syllabus can be the key to successful teaching. With a good syllabus, teachers and students will more easily achieve the learning objectives as set out in the curriculum. The syllabus is a source of information for students. The purpose of this study is to examine the development of an Arabic language learning syllabus. This research method uses a literature review technique approach. The data collection technique is through reviewing books, journal articles, and other scientific works which are then analyzed thematically. The results of the study indicate that this Arabic language learning syllabus still requires elaboration in a more concrete form in the form of a lesson plan (RPP), because the syllabus contains the general learning process for one semester. Elements that need to be developed in the syllabus are the syllabus identity, SK, KD, indicators, time allocation, materials / teaching materials, learning methods and media used, and books / learning resources needed. Because language learning has different characteristics from exact learning, it has its own syllabus design. However, the language learning syllabus also varies, including grammatical/structural syllabus, situational syllabus, notional/functional syllabus, topical syllabus, skills syllabus, process syllabus, task-based procedural syllabus, and mixed syllabus.